Stem Cell Therapy in Wound Healing and Tissue Regeneration - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: Recent advances in our basic knowledge of the tissue damage and regeneration pathology have combined with a remarkable progress in stem cell biology so the prospect of clinical tissue repair strategies is a tangible reality. We tried to describe a better view about mesenchymal stem cell (MSC) mechanisms in wound healing and tissue regeneration, sending any ideas for next advanced therapies.CONTENT: Sustaining injury, whether minor or major, is part of every organism life. Therefore, efficient response mechanisms to damage have developed. Wound healing is a perplexing multi-step processes which can be divided into three major phases: inflammation, proliferation, and scar formation/remodeling. Though the compartementalization of this process into discrete stages give the illusion of simplicity, but in reality it is much more complicated. So that efficient healing can occur, complex interactions between multiple cell types, soluble factors and extracellular matrix components are required to rebuild the tissue. Even under optimal conditions, the healing process drives to fibrosis or scar. The latest technology that makes a huge difference in the wound healing process is stem cell therapy, which offers a novel approach to many diseases.SUMMARY: Wound healing therapies continue to rapidly evolve, with advances in basic science and engineering research heralding the development of new therapies, as well as ways to modify existing treatments. Stem cell-based therapy is one of the most promising therapeutic concepts for wound healing. Advances in stem cell biology have enabled researchers and clinicians alike with access to cells capable of actively modulating the healing response. KEYWORDS: wound healing, tissue regeneration, stem cells therapy